A comparison of the stock structures of two exploited demersal teleosts, employing complementary methods of otolith element analysis - Fairclough, D.; Edmonds, J.; Jackson, G.; Lenanton, R.; Kemp, J.; Molony, B.; Keay, I.; Crisafulli, B.; Wakefield, Corey (Elsevier, 2013)
Complementary methods of otolith element analysis (IRMS of stable isotopes and laser ablation ICP-MS of trace elements) were used to elucidate the stock structures in Western Australia of the exploited demersal West Australian dhufish Glaucosoma hebraicum and Snapper Pagrus auratus. Residency of adults during their most recent part of life and the existence of important nursery locations were investigated by analysing otolith margins and cores, respectively, to evaluate the applicability of current spatial management. Stable oxygen isotope ratios (18O/16O) in both margins and cores of G. hebraicumotoliths increasedwith latitude and thus decreasing mean annual water temperature. Analyses of d18O, stable isotope composition (SI; d18O, d13C) and trace element composition (TE; 25Mg, 88Sr, 138Ba) in otolithmargins of G. hebraicumfromfourmanagement areas on the west coast of Australia indicated that adultswere resident in each area. Analyses of elements in otolith cores demonstrated that, by the early juvenile stage (b1 year old), individuals will have recruited to the area where they will remain as adults.Analyses of d18O and both SI and TE compositions in otolithmargins of adult P. auratus indicated residency within each of three large bioregions (Gascoyne,GCB;West,WCB; South, SCB) along thewest and south coasts ofwestern Australia. As for G. hebraicum, the data also demonstrated residency at the finer scale, i.e. within the fourmanagement areas on the west coast. The lack of a conspicuous pattern in d18Olevels in P. auratus otolith cores implied that adults in each area recruited from a range of nurseries. Although both SI and TE composition demonstrated that there was substantial self-recruitment within theWCB and SCB and within two of the four areas of theWCB, stock(s) of P. auratus at the southern extent of the GCB are likely to be partially reliant on immigration. Elemental signatures in otoliths of G. hebraicum and P. auratus demonstrated that adults in each management area of the WCB could be treated as separate stocks. However, while recruitment of juvenile G. hebraicum to adult stocks would occur primarily from adjacent multiple nurseries within areas of the WCB, adult P. auratus in any one bioregion and at least two of the four areas within the WCB were derived from arangeofnurseries, including across area and bioregion boundaries.